1997
DOI: 10.1021/jp963349a
|View full text |Cite
|
Sign up to set email alerts
|

Prompt and Delayed Electron Ejection from Photoexcited Aqueous Bromo- and Chlorocuprate(I) Complexes

Abstract: Two different routes for ejection of hydrated electrons by photoexcited CuCl 2 -and CuCl 3 2-have been observed: (1) a prompt (i.e. within the 5-ns laser pulse width) ejection directly from the charge-transfer excited states (characterized as CTTS or Rydberg states), and (2) a delayed ejection, with lifetimes of up to 105 ns, from the triplet states of the two complexes. These two processes have rather high quantum yields: 0.30-0.40 for the prompt ejection and 0.25-0.33 for the delayed ejection for the chloroc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 29 publications
(53 reference statements)
0
6
0
Order By: Relevance
“…Monomeric copper(I) complexes, CuL n , where n = 2 or 3 and L = Cl - , Br - , I - , NH 3 , CH 3 NH 2 , C 2 H 5 NH 2 , and CN - and mixtures thereof, have been shown to undergo very efficient photoinduced electron ejection, when irradiated into their charge-transfer-to-solvent (CTTS) bands, with quantum yields on the order of 0.2−0.3. Interestingly, room-temperature luminescence is observed along with the electron ejection only when halo ligands are present in the complex, and this has been ascribed to the formation of exciplexes in an excited-state equilibrium. Because of their very large stability constants, , the cyano complexes of copper(I), Cu(CN) 2 - , Cu(CN) 3 2- , and Cu(CN) 4 3- , are quite robust and air-stable in aqueous solution and can be formed, especially in the case of the first two, essentially by the quantitative reaction of copper(I) salts, such as CuCl or CuCN, with aqueous solutions of KCN or NaCN.…”
Section: Introductionmentioning
confidence: 99%
“…Monomeric copper(I) complexes, CuL n , where n = 2 or 3 and L = Cl - , Br - , I - , NH 3 , CH 3 NH 2 , C 2 H 5 NH 2 , and CN - and mixtures thereof, have been shown to undergo very efficient photoinduced electron ejection, when irradiated into their charge-transfer-to-solvent (CTTS) bands, with quantum yields on the order of 0.2−0.3. Interestingly, room-temperature luminescence is observed along with the electron ejection only when halo ligands are present in the complex, and this has been ascribed to the formation of exciplexes in an excited-state equilibrium. Because of their very large stability constants, , the cyano complexes of copper(I), Cu(CN) 2 - , Cu(CN) 3 2- , and Cu(CN) 4 3- , are quite robust and air-stable in aqueous solution and can be formed, especially in the case of the first two, essentially by the quantitative reaction of copper(I) salts, such as CuCl or CuCN, with aqueous solutions of KCN or NaCN.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, inorganic exciplexes have been recognized only recently . Recent reported examples involve coordination compounds of Pt(II), , Cu(I), 9c,, Ru(II), and Ir(III) .…”
Section: Introductionmentioning
confidence: 99%
“…We have previously reported the prompt and delayed UV photoejection of hydrated electrons from aqueous solutions of di- and trihalo anionic complexes of copper(I) with chloro , and bromo 2 ligands. The source of the prompt electron is attributed to direct ejection following excitation into the charge-transfer-to-solvent (CTTS) states of the complexes, whereas the delayed electron is ejected from two weakly luminescent, triplet, excited-state equilibrated species, a short-lived dihalo and a longer-lived trihalo complex, designated an exciplex. Similarly to the halocuprate systems, copper(I) forms di- and triammine complexes, according to the equilibrium ( K = 0.040) In an equilibrated mixture of these complexes, only the triammine species absorbs the laser UV output at 266 nm appreciably, also resulting in the ejection of hydrated electrons but without any accompanying luminescence. , Earlier laser flash studies at 266 nm revealed, along with the time-resolved spectrum of hydrated electrons, some other long-lived intermediate absorbing at about 400 nm .…”
mentioning
confidence: 99%
“…The absorption peak at about 720 nm is clearly that of the hydrated electron, and by comparison of this peak to the electron signal produced by a ferrocyanide actinometer solution the quantum yield for this prompt electron photoejection is estimated to be about 0.3. Since earlier CW experiments 7,9 showed that the species oxidized by UV light in a solution of copper(I) in ammonia is the triamminecopper(I) cation, the primary photochemical step is absorption into the CTTS (or Rydberg d → s or d → p) state and prompt ejection of an electron, The electron is scavenged by the two copper(I) ammine complexes presumably forming copper(0) ammine species which appear to absorb around 400 nm, similarly to their halocuprate counterparts. , At very low or very high copper concentrations the electron decay is simple first order, but there is an intermediate range of copper concentrations where the signal becomes biexponential (see below). The initial decay lifetime of this electron signal decreases as the copper(I) concentration is increased, and from the slope of a plot of the observed electron decay constant vs [Cu(I)] (not shown) we obtain, at this ammonia concentration, the second-order scavenging constant of 3.0 × 10 9 M -1 s -1 .…”
mentioning
confidence: 99%
See 1 more Smart Citation